Pengaruh Budaya, Sosial, Pribadi dan Psikologis Terhadap Keputusan Pembelian Durian Dengan Sistem Ijon - Adinugraha, Hendri Hermawan; Fikri, Muhammad Khoirul; Sukirno, Sukirno (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2021)
Cultural, social, personal, and psychological are consumer behavior factors in buying and selling transactions, especially buying and selling durian using the bonded bond system in Lemahabang Village. In practice, buying and selling of durian using the bonded system is carried out by both parties when the fruit is still on the tree, so the quality and quantity are not known. The purpose of this study was to determine how much cultural, social, personal, and psychology influence the purchase decision for durian with the bonded system. This study uses multiple linear regression analysis using the SPSS program. The population in this study were all durian farmers who were durian buyers with the bonded bond system in Lemahabang Village whose numbers were unknown or infinite. The sampling technique uses incidental sampling and the determination of the number of samples using the Lemeshow formula, which is a total of at least 100 samples. The data collection method used a questionnaire. The results showed that partially cultural, social, personal, and psychological factors had a significant and positive effect and positive relationship between the independent variables on durian purchasing decisions with the bonded system. Simultaneously, culture, social, personal, and psychological factors influence on durian purchasing decisions with the results of f count of 45.106> f table of 2.47 and a significant value of 0.000 <0.05.